2018
DOI: 10.1063/1.5023316
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-dependency of the optical band gap of ZnO measured by electron energy-loss spectroscopy in a scanning transmission electron microscope

Abstract: The optical band gap of ZnO has been measured as a function of temperature using Electron Energy-Loss Spectroscopy (EELS) in a (Scanning) Transmission Electron Microscope ((S)TEM) from approximately 100 K up towards 1000 K. The band gap narrowing shows a close to linear dependency for temperatures above 250 K and is accurately described by Varshni, Bose-Einstein, P€ assler and Manoogian-Woolley models. Additionally, the measured band gap is compared with both optical absorption measurements and photoluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
3
5
0
Order By: Relevance
“…The standard deviation is below 0.01 eV based on 19 measurements in the ZnO layer, and we therefore consider this variation to be significant. This is also consistent with the optical band gap of ZnO and its temperature dependence as previously found by EELS [36], as well as by other conventional band gap methods [37]. In samples with high enough electron concentrations, such as ours, the Fermi level moves into the conduction band and thus states below this level are filled and not available for optical transitions from the valence band.…”
Section: B Band Gap Analysissupporting
confidence: 90%
“…The standard deviation is below 0.01 eV based on 19 measurements in the ZnO layer, and we therefore consider this variation to be significant. This is also consistent with the optical band gap of ZnO and its temperature dependence as previously found by EELS [36], as well as by other conventional band gap methods [37]. In samples with high enough electron concentrations, such as ours, the Fermi level moves into the conduction band and thus states below this level are filled and not available for optical transitions from the valence band.…”
Section: B Band Gap Analysissupporting
confidence: 90%
“…The apparent band gap, E g , for ZOGN thin films was estimated using transmission measurements, as well as STEM-EELS, both yielding a significant reduction down to ∼2.4 -2.6 eV for x ≤ 0.15. Using EELS represented as spatially resolved maps discriminating ∼5 nm pixels [96] together with EDX maps, it was furthermore found that the reduction in apparent E g was close to homogeneous over the probed area, with no indications of segregation into ZnO-or GaN phases with band gap energies of ∼3.4 -3.5 eV. Our experimentally obtained band bowing is also in remarkable agreement with our theoretically obtained results, utilizing the GW approximation.…”
Section: Band Gap Evolution In (Zno) 1−x (Gan) X Alloyssupporting
confidence: 86%
“…2 probe regions of ∼150 μm in diameter and 200 × 400 nm 2 , respectively. The EELS data can also be presented in the form of spatially resolved maps discriminating ∼5 nm pixels [39]. Figure 4 shows (a) an example of such map for x = 0.15, (b) onset for a number of pixels as indicated by arrows in the map, and (c) corresponding dark-field image of the mapped area of the sample.…”
Section: A Experimental Resultsmentioning
confidence: 99%